The Future of Adaptive Learning Systems in Education - Siswanti, Tri; Chai, Napat; Som, Rit (Journal International Inspire Education Technology, 2025)
The rapid advancement of artificial intelligence (AI) and data-driven technologies has revolutionized education, paving the way for adaptive learning systems that personalize instruction based on individual learner needs. Traditional one-size-fits-all teaching methods often fail to accommodate diverse learning paces, styles, and abilities, necessitating more dynamic and responsive educational solutions. Adaptive learning systems leverage AI algorithms, real-time analytics, and machine learning to deliver customized learning experiences, enhancing student engagement and knowledge retention. This study aims to evaluate the effectiveness and future potential of adaptive learning technologies in education by analyzing their impact on learner outcomes, engagement, and instructional efficiency. A mixed-methods research approach was employed, integrating experimental assessments, student surveys, and instructor interviews across various educational institutions. Findings indicate that adaptive learning systems significantly improve student performance by tailoring instructional content, providing real-time feedback, and optimizing learning pathways. Statistical analysis revealed strong correlations between adaptive learning features and enhanced academic achievement. The study concludes that adaptive learning will play a transformative role in the future of education, requiring continuous refinement, ethical considerations, and policy development for broader implementation. Future research should explore long-term impacts and best practices for integrating AI-driven education across diverse learning environments.